Pengaruh Harga, Kualitas Produk Dan Cita Rasa Terhadap Kepuasan Konsumen Belfoods - Dewi Panglipur Ati; Sriwahyuni Mega Hastuti (Otonomi, 2022)
The goal to be achieved by the author in this study is to determine the influence between price, product quality, and taste on Belfoods consumer satisfaction on Dewi Freezeen. In this study, the population is all consumers who have purchased and or consumed Beelfoods products on the Dewi Frozen oulet addressed at Jl. Mawar RT /RW: 003/005 – Dsn. Tawang Sari – Ds. Gempolan – Kec. Gurah – Keb. Kediri. The sample in this study was 80 respondents, with sampling using the Accidental Sampling method which collected data with questionnaires and conducted interviews and observations. Meanwhile, the data analysis used is by descriptive analysis and SPSS analysis with testing: Validity, Reliability, Classical Assumptions (Normality, Multicholinearity, Heteroskedasticity), Multiple Linear Regression, Hypothesis Test (t and f), and Coefficient of Determination test. The results of data analysis and hypothesis testing showed that price partially had no significant effect on Belfoods consumer satisfaction. Meanwhile, the variables of product quality and taste partially have a significant effect on Belfoods consumer satisfaction, then simultaneously the variables of price, product quality and taste have a significant effect on Belfoods consumer satisfaction at Dewi Frozeen.